Developing Local Genius-based English E-Module for Vocational High School Students in Jambi City - Fitri, Nurul; Satria, Willy (Universitas Batanghari Jambi, 2026)
This study aims to develop a local genius-based English e-module for vocational high school students majoring in hospitality at SMK Negeri 1 Jambi City. The development of this e module was motivated by the need to provide contextual and culturally relevant English learning materials that align with the Merdeka Curriculum principles. The e-module integrates Jambi’s local wisdom, such as tourism destinations, traditional cuisine, and cultural heritage into language learning tasks designed for hospitality contexts. This research employed the Research and Development (R&D) method adapted from Borg and Gall (1983), involving six stages: needs analysis, design, development, expert validation, revision, and try-out. Data were collected through questionnaires, interviews, and validation sheets. The e-module underwent validation by material and media experts and was tested with a group of Grade 10 hospitality students. The results showed that the developed e-module achieved a “Very Good” level of feasibility in terms of content, design, and practicality. Students reported higher motivation and engagement when learning English through local contexts. The findings indicate that integrating local genius into English learning supports students’ communication skills and cultural awareness, while making learning more meaningful and enjoyable.